The immune-checkpoint HLA-G/ILT4 is involved in the regulation of VEGF expression in clear cell renal cell carcinoma - García, Marcela (2020)
Background: Clear cell renal cell carcinoma (ccRCC), the most aggressive renal cancer, is characterized by early lymph node metastases and bad prognosis. Most therapies targeting advanced or metastatic ccRCC are based, as first-line treatment, on the administration of the vascular endothelial growth factor (VEGF) neutralizing antibody termed Bevacizumab. Despite proven benefits, the expected results were not obtained for the majority of patients. The possibility that an intricate interplay between angiogenesis and immune-checkpoints might exist lead us to evaluate tumor angiogenesis, by means of VEGF expression together with the immune checkpoint HLA-G/ILT4. Methods: Tumor specimens were obtained from patients from two separate cohorts: One from "Evita Pueblo"Hospital from Berazategui, (Buenos Aires, Argentina) and the second includes patients surgically operated at the Urology Department of Saint-Louis Hospital (Paris, France) with a confirmed ccRCC diagnosis. Immunohistochemistry was performed with specific antibodies directed against HLA-G, VEGF-A, VEGF-C, D240, CD34, ILT4 and Ca-IX. In addition, gene expression levels were measured in a cell line derived from a ccRCC patient by semi-quantitative RT-PCR. Results: Our results show that the highly vascularized tumors of ccRCC patients express high levels of VEGF and the immune-checkpoint HLA-G. In addition, ILT4, one of the HLA-G receptors, was detected on macrophages surrounding tumor cells, suggesting the generation of an immune-tolerant microenvironment that might favor tumorigenesis. Notably, RT-qPCR analysis provided the first evidence on the transcriptional relationship between HLA-G/ILT4 and the VEGF family. Namely, in the presence of HLA-G or ILT4, the levels of VEGF-A are diminished whereas those of VEGF-C are increased. Conclusions: In an effort to find new therapeutic molecules and fight against metastasis dissemination associated with the poor survival rates of ccRCC patients, these findings provide the rationale for co-targeting angiogenesis and the immune checkpoint HLA-G.